Identification of quantitative trait loci (QTLs) associated with agronomic traits in tea (Camellia sinensis) (L.) O. Kuntze - Apostolides, Zeno (University of Pretoria, 2026)
Dissertation (MSc)--University of Pretoria, 2019.